2013
DOI: 10.1371/journal.pone.0055067
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Alternative Evidence Summary and Presentation Formats in Clinical Guideline Development: A Mixed-Method Study

Abstract: BackgroundBest formats for summarising and presenting evidence for use in clinical guideline development remain less well defined. We aimed to assess the effectiveness of different evidence summary formats to address this gap.MethodsHealthcare professionals attending a one-week Kenyan, national guideline development workshop were randomly allocated to receive evidence packaged in three different formats: systematic reviews (SRs) alone, systematic reviews with summary-of-findings tables, and ‘graded-entry’ form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
67
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(69 citation statements)
references
References 18 publications
2
67
0
Order By: Relevance
“…The authors found that the threepage summary format with supporting contextual information was the most preferred source of systematic review knowledge to inform policy-making (49% of respondents) as compared to the one-page summaries (23%), the full journal article (15%), and a quantitative ''summary-of-findings'' table format (13%) (Pham et al, 2013). These results correspond to similar findings in the health sector, indicating that end-users prefer to receive systematic review knowledge in a contextualized plain-language format (Lavis et al, 2005;Rosenbaum et al, 2011;Opiyo et al, 2013). Additional research is necessary to evaluate the utility of these summary formats further among different populations of end-users in this sector.…”
supporting
confidence: 83%
See 2 more Smart Citations
“…The authors found that the threepage summary format with supporting contextual information was the most preferred source of systematic review knowledge to inform policy-making (49% of respondents) as compared to the one-page summaries (23%), the full journal article (15%), and a quantitative ''summary-of-findings'' table format (13%) (Pham et al, 2013). These results correspond to similar findings in the health sector, indicating that end-users prefer to receive systematic review knowledge in a contextualized plain-language format (Lavis et al, 2005;Rosenbaum et al, 2011;Opiyo et al, 2013). Additional research is necessary to evaluate the utility of these summary formats further among different populations of end-users in this sector.…”
supporting
confidence: 83%
“…We developed the guideline and summary formats based on a review and evaluation of existing plain-language and contextual summaries in health and other sectors (Canadian Foundation for Healthcare Improvement, 2010; Rosenbaum et al, 2011;Khangura et al, 2012;Health Evidence, 2013;Opiyo et al, 2013;ResearchImpact, 2014). The one-and three-page formats were prioritized based on consultation with end-users who indicated preference for graded-entry summaries (i.e., multiple layers of short and longer summaries) and the addition of contextual information to highlight the relevance of the systematic review findings for decision-making (Rosenbaum et al, 2011;Khangura et al, 2012;Opiyo et al, 2013). The target end-users for the summaries includes professionals working at the science-to-policy interface in the agri-food public health sector, which we define as policy-makers and those who support them (e.g., policy and research analysts), practitioners, extension personnel, program officers and specialists, and other government and industry decision-makers .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Five systematic reviews (from seven articles) [18, 19, 21, 30–33] and one primary study with a strong study design – a RCT [34] – met the inclusion criteria for the review. The selection process for studies and the numbers at each stage are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…There have also been promising developments in clinical guideline development and evaluation in the African region [13,19,20]. For example, Kredo and co-authors [19], assessed 30 regional guidelines from 13 countries linked to five priority diseases and found quality gaps in relation to the AGREE II tool and variable concordance with current best evidence.…”
Section: Ebhc In Africa: the Past 2 Decadesmentioning
confidence: 99%